Competencias y metacompetencias de los periodistas digitales (Monográfico) - Cruz, Jorge (2020)
The profile of journalists and their competences can be reviewed in the light of the advances that digital technology has introduced in the profession. This paper aims to find a model for the construction of competencies and meta-competencies that deal with cognitive, personal, social and ethical elements. On the map of these skills the visions of scholars of digital culture, as well as academics related to cyber journalism will be placed. The objective will be to find a better understanding and a fresh vision on which areas should be rethought in the training and consideration of the profiles of journalists in the present and in the face of the coming changes.